Fruit Quality Attributes of Organically Grown Norwegian Apples Are Affected by Cultivar and Location - Maja Natić; Dragana Dabić Zagorac; Mihajlo Jakanovski; Anita Smailagić; Slavica Čolić; Mekjell Meland; Milica Fotirić Akšić (Plants, 2024)
In this work, 12 apple cultivars grown organically in three regions of Norway (Telemark, Ullensvang, Viken) were analyzed in terms of fruit quality, with the aim of equating different growing regions under specific climatic conditions. Apples were analyzed for concentration levels of minerals, sugars, sugar alcohols, organic acids, total phenolic content (TPC), radical scavenging activity (RSA), and phenolic profiles. Discovery “Rose” from Telemark stored the highest level of minerals (24,094.5 mg/kg dry weight). Glucose, fructose, sucrose, and sorbitol were the major carbohydrates, whereas the predominant organic acids were quinic acid and malic acid. Cultivar Discovery from Ullensvang had the highest TPC (9.22 g/kg) and RSA (229.32 mmol TE/kg). Of the polyphenols quantified, chlorogenic acid and kaempferol-3-O-glucoside were the most abounded, accounting for 85.50%. Principal component analysis (PCA) shows that the Ullensvang region is the richest source of most carbohydrates, organic acids (quinic, shikimic, and galacturonic), and most polyphenols, whereas the highest content of minerals and maleic acid characterized Viken. Regardless of location, the Discovery cultivar had, on average, the highest sugar and polyphenol contents. The results obtained suggest that organic apples from Norway are a rich source of beneficial compounds that can have a positive impact on human health. In addition, these results may be useful for consumers in identifying apple cultivars with desirable characteristics and for the fruit industry in tracing back the origin of apples. The findings could also be of great interest for locations with similar climate and soil conditions worldwide.